Synthesis and characterization of starch nanoparticles and carbon nanodots - Siti Nur Akmar, Binti Mohd Yazid (University Malaysia Sarawak, UNIMAS, 2013)
Starch is a well-known, versatile, and inexpensive biopolymer and it is a promising precursor material for preparation of nanoparticles. In this research, starch nanoparticles were synthesized from native sago starch and the potential applications of these starch nanoparticles as controlled release carriers were evaluated. Curcumin was loaded into starch nanoparticles by using a simple precipitation in water-in-oil microemulsion approach. The effects of synthesis parameters such as types of reaction medium, types of surfactant and its concentrations, oil/ethanol ratios and curcumin concentration were found to affect the particle sizes, morphology and loading efficiency of the curcumin loaded starch nanoparticles. Curcumin was observed to release out from starch nanoparticles in a slow and sustanable way over the period of 10 days. In addition, these starch nanoparticles were used as precursors for the synthesis of fluorescent carbon nanodots (C-dots). The C-dots were synthesized by carbonization and surface oxidation of preformed sago starch nanoparticles. The fluorescence of these C-dots were found to be significantly quenched in the presence of Sn(II) ions, and such changes could therefore be utilized as a highly sensitive sensing probe for detecting Sn(II) ions. Parameters which influence the sensing characteristics of the C-dots probe had been optimized with its highest fluorescence intensity obtained at an optimum concentration of 1.75 mM in aqueous solution. The C-dots probe was highly selective and exhibited low interference responses towards several heavy metal ions tested. Based on spectroscopic study, the fluorescence quenching mechanism appeared to be predominantly of the static type compared to the dynamic one. Under optimum conditions, the probe exhibited a linear response range of Sn(II) ions concentration up to 4.00 mM, and with a detection limit (LOD) of 0.36 μM.